the centre of (x - 2)^2 + (y + 1)^2 = 16
is (2,-1)
Now move that centre 4 units to the left and 6 units up
New centre is .......
new equation is .......
What is an equation for the translation (x - 2)^2 + (y + 1)^2 = 16 by 4 units left and 6 units up?
1) (x + 2)^2 + (y - 5)^2 = 16
2) (x - 2)^2 + (y - 5)^2 = 16
3) (x + 5)^2 + (y - 2)^2 = 16
4) (x + 4)^2 + (y - 5)^2 = 16
9 answers
They mean the answer is A. Just took the assignment.
Does anyone have the whole test?
Anybody have the answers to the whole test
Legend has it that Anonymous is still looking for the test answers to this day
Anyone have answers to whole test?
I got yall hold up
Nvm the questions are different for everyone
i mean u could just write out the entire question and put the answer in